IMPLEMENTATION OF GENETIC ALGORITHM BASED ON JAVASCRIPT IN OBJECT ROUTING SHORTEST TOUR ON TIMOR ISLAND - Simarmata, Justin Eduardo; Mone, Ferdinandus (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
The purpose of this study is to apply a genetic algorithm using a programming language that can be used to determine the shortest route to tourist attractions in Timor Island, East Nusa Tenggara. The application of genetic algorithms expected to be able to obtain the shortest route information that is most effective, the route that do not take a long time for tourists, and the presentation of route information for tourists. The method used is genetic algorithm to build the shortest route system for tourist attractions in Timor Island. The results of the system application shown that the optimization of travel routes that have been built can provide convenience in choosing tourist travel routes in Timor Island. Route optimization can help the process of making routes from the first location of departure and the attractions to be visited. The system is also used to assist domestic tourists in getting to know the attractions of Timor Island for solutions the shortest route.